On the issue of criminal law protection of cyber security of Ukraine in modern conditions - Chuvakov O. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. Taking into account the existing threats to the foundations of the national and military security of Ukraine and in the conditions of rapidly changing geopolitical realities, there is a need to improve the existing criminal policy of the state, as well as some provisions of criminal legislation in the field of proper protection of such objects of criminal law protection against cyber attacks. Methodology. The methodological basis of the research is a set of general scientific principles and approaches, philosophical-worldview and special-scientific methods of learning socio-legal processes and phenomena, including: historical, dogmatic, comparative-legal, formal-logical, systemic-structural, modeling method. Results. In the process of research, it was established the need to improve a number of provisions of the Special Part of the Criminal Code of Ukraine, which will allow strengthening measures of criminal repression in relation to anti-state offenses carried out through cyber attacks, and, accordingly, to reorient the methodological foundations of the existing criminal policy of our state with regard to the severity of criminal repression measures in order to localize such anti-state criminal manifestations in modern conditions. This provision allows to some extent to improve the current criminal legislation on countering cyber attacks on the bases of national and military security of Ukraine, and therefore to significantly increase the effectiveness of combating them at the current stage of such protection of the objects under consideration. Originality. In the process of research, a scientifically based concept of criminal law protection of the foundations of national and military security of Ukraine was developed, which defines new directions of the existing criminal policy of the state in this area, and also contains a number of proposals for improving some provisions of the current criminal legislation in the field of cyber security protection of Ukraine. Practical significance. The results of the research can be used in law-making and law-enforcement activities during the investigation of crimes related to the use of modern means of electronic communications, information and communication technologies, software, hardware and other technical and technological means and equipment against the foundations of national and military security of Ukraine.